2021
DOI: 10.3390/nu13082487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Protein-Rich Nutritional Composition Supplementation on Sarcopenia Indices and Physical Activity during Resistance Exercise Training in Older Women with Knee Osteoarthritis

Abstract: Older adults with knee osteoarthritis (KOA) are at high risk of sarcopenia. Protein-rich nutritional composition supplementation (PS) combined with resistance exercise training (RET) improves muscle gains and facilitates physical activity in older adults. However, whether PS augments the effects of RET on muscle mass and PA in patients with KOA remains unclear. Therefore, this study identified the effects of PS on sarcopenic indices and PA in older women with KOA subjected to an RET program. Eligible older wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 141 publications
0
14
0
Order By: Relevance
“…Participants undergoing a 12-week program of resistance exercise, protein supplementation, and vitamin D supplementation achieved the most substantial improvement in muscle quality and strength, among sarcopenic or dynapenic older adults [36]. A study by Liao and colleagues investigated the e cacy of a combined intervention involving resistance exercise training and protein supplementation in promoting the recovery of walking speed among individuals with knee osteoarthritis and sarcopenia [37] and found that the 12-week treatment enhanced the therapeutic effects by accelerating the time required for walking speed recovery to a level equal to or greater than 1.0 m/s. This improvement in walking speed not only helps reduce the severity of the disease but also has the potential to minimize the risk of sarcopenia in these patients [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants undergoing a 12-week program of resistance exercise, protein supplementation, and vitamin D supplementation achieved the most substantial improvement in muscle quality and strength, among sarcopenic or dynapenic older adults [36]. A study by Liao and colleagues investigated the e cacy of a combined intervention involving resistance exercise training and protein supplementation in promoting the recovery of walking speed among individuals with knee osteoarthritis and sarcopenia [37] and found that the 12-week treatment enhanced the therapeutic effects by accelerating the time required for walking speed recovery to a level equal to or greater than 1.0 m/s. This improvement in walking speed not only helps reduce the severity of the disease but also has the potential to minimize the risk of sarcopenia in these patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Liao and colleagues investigated the e cacy of a combined intervention involving resistance exercise training and protein supplementation in promoting the recovery of walking speed among individuals with knee osteoarthritis and sarcopenia [37] and found that the 12-week treatment enhanced the therapeutic effects by accelerating the time required for walking speed recovery to a level equal to or greater than 1.0 m/s. This improvement in walking speed not only helps reduce the severity of the disease but also has the potential to minimize the risk of sarcopenia in these patients [37]. In another RCT, performing thirty minutes of heavy-load strength training three times per week, along with protein supplementation, resulted in increased leg lean mass, as well as improvements in strength and functional capacity among older adults with limited mobility [38].…”
Section: Discussionmentioning
confidence: 99%
“…A spectrum of therapeutic strategies has emerged from this recognition. These encompass methodologies such as isokinetic exercises 33 and a combination of nutritional interventions with resistance training, 34 all directed toward augmenting the muscular strength of KOA patients, thereby aiming to alleviate their symptoms. Concurrently, a myriad of research articles has highlighted the pervasive nature of muscular strength deficiencies observed among KOA patients, regardless of the severity of their individual conditions.…”
Section: Muscle Strengthmentioning
confidence: 99%
“…Among the various exercise training regimens for older individuals, resistance exercise training (RET) has demonstrated promising effects in terms of muscle mass gain, strength increase, and WS recovery in sarcopenia [ 39 , 40 , 41 ] and KOA [ 42 , 43 ]. In particular, an elastic RET using elastic strips or bands has been frequently used as a treatment method and is considered safe for muscle strengthening in elderly people with KOA [ 44 , 45 , 46 ]. In addition to exercise training, nutritional interventions such as protein supplementation (PS) are believed to augment the efficacy of exercise training for sarcopenia among older adults [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to exercise training, nutritional interventions such as protein supplementation (PS) are believed to augment the efficacy of exercise training for sarcopenia among older adults [ 47 , 48 , 49 , 50 , 51 ]. However, few studies have investigated the effects of PS plus RET (PS+RET) on older individuals with KOA [ 45 ]. WS may positively influence a detrimental effect of sarcopenia, namely dependency while performing activities of daily living [ 52 ], and therefore, increasing WS can increase the probability of recovery from disability [ 53 ] and reduce the need for long-term care [ 54 ].…”
Section: Introductionmentioning
confidence: 99%